Stable and Robust Recovery of Approximately $k$-Sparse Signals with Partial Support Information in Noise Settings via Weighted $ℓ_p\ (0 < p ≤ 1)$ Minimization (Journal of Computational Mathematics, 2023)
In the existing work, the recovery of strictly $k$-sparse signals with partial support information was derived in the $\u2113_2$ bounded noise setting. In this paper, the recovery ofapproximately $k$-sparse signals with partial support information in two noise settings is investigated via weighted $\u2113_p \ (0 < p \u2264 1)$ minimization method. The restricted isometry constant (RIC) condition $\u03b4_{tk}